(untitled) (gjstudies, 2017)
This research investigates the underexplored causal relationship between the timelinessof corporate financial reporting and the subsequent efficiency of market information processing, proposing a novel methodological framework that diverges from traditional event-studyand market microstructure approaches. We introduce the concept of ’Temporal InformationAbsorption Capacity’ (TIAC), a metric derived from the convergence of information theoryand behavioral finance, to quantify how swiftly and completely market prices incorporatethe informational content of financial statements based on their release latency. The studyformulates three primary research questions: (1) Does a non-linear, threshold-based relationship exist between reporting delay and market efficiency degradation? (2) Can early signalsof inefficiency, manifesting as anomalous cross-asset return correlations, be detected in thepre-announcement period of delayed reports? (3) Does the market’s penalization of tardinessexhibit asymmetric properties contingent on underlying macroeconomic volatility regimes?Our methodology employs a hybrid computational model combining agent-based simulationcalibrated with historical SEC filing data and a proprietary algorithm for parsing the ’information density’ of financial statements. We construct a unique dataset spanning 1998-2004,linking EDGAR filing timestamps with high-frequency trades and analyst forecast revisions.Results indicate a critical threshold of 5 business days beyond the typical filing date, after which TIAC decays exponentially, leading to measurable mispricing. Furthermore, weidentify a ’contagion effect’ wherein delays from firms in central network positions (basedon shared analyst coverage) impair the price discovery of connected firms. The findingscontribute original insights to the literature by re-conceptualizing timeliness not merely asa compliance attribute but as a dynamic determinant of systemic information processinghealth, with novel implications for regulatory policy and real-time disclosure technologies.